Application of Qualitative Content Analysis in User-Program Interaction Research - Christian Spannagel; Michaela Gläser-Zikuda; Ulrik Schroeder (Forum: Qualitative Social Research, 2005)
This article describes how techniques of qualitative content analysis (QCA) can be applied to analyze user actions. Criteria for a software system supporting QCA of user-program interactions are systematically developed. A software tool is presented which allows recording and replaying user actions. In addition, it supports the application of QCA on recorded action sequences. Two approaches of category specification in analysis are discussed—inductive category development and deductive category application—which may be transferred to the area of user action analysis. The procedure for the analysis of user behavior and consequences for further development of the software system are discussed. URN: urn:nbn:de:0114-fqs0502295